Design and Development of Web-Based USV Ground Control Station for Ocean Observation - Ali Musthofa Baharudin; Setyawan Ajie Sukarno; Mohammad Harry Khomas Saputra (International Journal of Marine Engineering Innovation and Research, 2026)
Ocean observation increasingly relies on Unmanned Surface Vehicles (USVs) for wide-area maritime data collection, yet existing Ground Control Station (GCS) systems remain limited by desktop-based accessibility constraints, high-latency HTTP communication, unoptimized relational databases, and the absence of integrated oceanographic sensor visualization. This study aims to design and develop a web-based GCS that unifies telemetry monitoring, bidirectional remote control, CTD and ADCP sensor visualization, and waypoint-based mission planning within a single browser-based interface. The system was developed using the Rapid Application Development (RAD) methodology, with MQTT and WebSocket adopted for low-latency communication and PostgreSQL with TimescaleDB for time-series data management. Functional testing confirmed that all core features operated correctly. Performance evaluation under 4G-LTE field conditions showed an average command round-trip latency of 178 ms and end-to-end monitoring latency below 250 ms. TimescaleDB hypertable conversion improved write throughput by 2.5×, reduced long-range query latency by 3.75×, and achieved a storage compression ratio of 875×. The proposed architecture provides a replicable reference for web-based USV GCS development across ocean observation applications.